Subjetividad y donación en Jean-Luc Marion - Walton, Roberto J. (ARFIL y UNL, 2018)
This article sets out to establish the distinctive traits of the three stages of the erotic reduction advanced by J.-L. Marion in contrast to the epistemic reduction to the cogito and the ontological reduction to Being. First, in the search for an assurance involving the other, the self-certainty of the cogito is replaced by the question ¿Am I loved from elsewhere?. Second, as the question cannot be answered by the way of self-love, a radicalized formulation must be given: ¿Can I love as the first one? This new stage brings forth the analysis of phenomena in which each partner gives the other what he does not have on his own and at the same time has at his disposal only to offer it to the other, i.e., meaning, flesh, pledge, joy, faithfulness, and goodby=God be with you. Third, as this logic of love discloses the priority of the other, a final formulation of the reduction is afforded: ¡You, you have loved as the first one! Marion contends that, through this precedence, God’s love is revealed. A final assessment of Marion's contributions outlines overlappings and contrasts with other phenomenological positions.